Sampling Rate of Heart Rate Variability Impacts the Ability to Detect Acidemia in Ovine Fetuses Near-Term - Durosier, L. Daniel; Green, Geoffrey; Batkin, Izmail; Seely, Andrew J.; Ross, Michael G.; Richardson, Bryan S.; Frasch, Martin G. (Frontiers in Pediatrics, 2014)
Background: To evaluate the impact of sampling rate on the predictive capability of continuous fetal heart rate (FHR) variability (fHRV) monitoring for detecting fetal acidemia during labour, we tested the performance of the root mean square of successive differences (RMSSD) in R-R intervals from the ECG when acquired with the sampling rate of 4 Hz currently available in FHR monitors, in comparison to the gold standard of 1000 Hz. Methods: Near-term ovine fetuses (N=9) were chronically prepared with precordial electrodes for recording ECG, vascular catheters for blood sampling, and an umbilical cord occluder. For 1 min every 2.5 min, animals underwent mild partial umbilical cord occlusions (UCO) x1 h, moderate partial UCO x 1h, then complete UCO x 2 h, or until arterial pH reached < 7.00. Arterial blood samples were drawn at baseline and every 20 min during the UCO series. RMSSD was calculated continuously in 5 min windows using an automated, standardized system (CIMVA.com). Results are presented as mean±SEM with significance assumed for P< 0.05. Results: Repetitive UCO resulted in pH decreasing from 7.35±0.01 to 7.00±0.03. In all 9 animals, RMSSD increased from 16.7±1.0 ms at baseline to 44.4±2.3 ms 70±15 min prior to reaching the pH nadir when sampled at 1000 Hz. When sampled at 4 Hz, RMSSD at baseline measured 36.1±6.0 ms and showed no significant increase during the UCO series until the pH nadir was reached. Consequently, early detection of severe hypoxic-acidemia would have been missed in all fetuses. Conclusions: RMSSD as a measure of fHRV when calculated from FHR sampled at 1000 Hz allowed for the early detection of worsening hypoxic-acidemia in each fetus. However, when calculated at the low sampling rate of 4 Hz used clinically, RMSSD remained unchanged until terminally when the nadir pH was reached. For early detection of fetal acidemia during labour, more sensitive means of acquiring FHR are therefore recommended than currently deployed.